COST OF CAPITAL DERIVED FROM LONG TERM DEBT - Pardamean H. Situmorang; Armen Siagian; Lizania Syahputri; Indrayani; Damsar; Muammar Khaddafi (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
Long-term debt is a policy that is often taken by companies in order to develop their business or invest in the form of fixed assets or non-fixed assets that are used as capital, because a company may not use all of its own capital to invest so that through long-term debt this is how the company can invest and from the results of that investment the company can repay its debts. The decision to take long-term debt requires careful calculation, how much the company's ability to invest and run its business operations, so that long-term debt is not a problem but makes the company grow and develop.